Changes in epidemiology of leptospirosis in 2003–2004, a two El Niño Southern Oscillation period, Guadeloupe archipelago, French West Indies - STORCK, C. HERRMANN (Cambridge University Press, 2008)
Our study aimed at analysing the changes in epidemiological features of leptospirosis cases from the hospital of Pointe à Pitre in Guadeloupe in 2003–2004 compared to reliable data in 1994–2001. Leptospirosis incidence increased fourfold during 2002–2004, a period with two El Niño events. Whereas the main risk factors were unchanged (male gender, occupational exposure, contact with cattle or pigs) a major role of rodent exposure emerged (52%, P=0·02, multivariate analysis). Interestingly, mean age of cases shifted to the older population (51·7 years vs. 43 years, P<0·05). Moreover, the Ballum serogroup rose dramatically (36% of incidence) competing with the Icterohaemorragiae serogroup (62%). However, severe forms were less recorded. Our data suggest that the changes in leptospirosis features could be related to exceptional meteorological events and their consequences on rodent populations. We propose the monitoring of rodent population and climatic data as a tool of management of leptospirosis in Guadeloupe.